Comparative study of the shear bond strength of composite resin bonded to enamel treated with acid etchant and erbium, chromium: Yttrium, scandium, gallium, garnet laser - Adel Sulaiman Alagl; Sumit Bedi; Khalid Sadiaq Hassan (Wolters Kluwer Medknow Publications, 2016)
Aim: The purpose of this investigation is in vitro comparison of the shear bond strength (SBS) of composite resin bonded to enamel pretreated with an acid etchant against enamel etched with erbium, chromium: yttrium, scandium, gallium, garnet (Er, Cr:YSGG) laser. Materials and Methods: Sixty premolars were sectioned mesiodistally and these 120 specimens were separated into two groups of 60 each (Groups A and B). In Group A (buccal surfaces), enamel surface was etched using 37% phosphoric acid for 15 s. In Group B (lingual surfaces), enamel was laser-etched at 2W for 10 s by Er, Cr:YSGG laser operational at 2780 nm with pulse duration of 140 μs and a frequency of 20 Hz. After application of bonding agent on all test samples, a transparent plastic cylinder of 1.5 mm × 3 mm was loaded with composite and bonded by light curing for 20 s. All the samples were subjected to SBS analysis using Instron Universal testing machine. Failure modes were observed under light microscope and grouped as adhesive, cohesive, and mixed. Failure mode distributions were compared using the Chi-square test. Results: SBS values obtained for acid-etched enamel were in the range of 7.12-28.36 megapascals (MPa) and for laser-etched enamel were in the range of 6.23-23.35 MPa. Mean SBS for acid-etched enamel was 15.77 ± 4.38 MPa, which was considerably greater (P < 0.01) than laser-etched enamel 11.24 ± 3.76 MPa. The Chi-square test revealed that the groups showed no statistically significant differences in bond failure modes. Conclusions: We concluded that the mean SBS of composite with acid etching is significantly higher as compared to Er, Cr: YSGG (operated at 2W for 10 s) laser-etched enamel.